On the origin of low‐energy electrons in the inner magnetosphere: Fluxes and pitch‐angle distributions. Issue 2 (15th February 2017) - Denton, M. H.; Reeves, G. D.; Larsen, B. A.; Friedel, R. F. W.; Thomsen, M. F.; Fernandes, P. A.; Skoug, R. M.; Funsten, H. O.; Sarno‐Smith, L. K.
Abstract: Accurate knowledge of the plasma fluxes in the inner magnetosphere is essential for both scientific and programmatic applications. Knowledge of the low‐energy electrons (approximately tens to hundreds of eV) in the inner magnetosphere is particularly important since these electrons are acted upon by various physical processes, accelerating the electrons to higher energies, and also causing their loss. However, measurements of low‐energy electrons are challenging, and as a result, this population has been somewhat neglected previously. This study concerns observations of low‐energy electrons made by the Helium Oxygen Proton Electron instrument on board the Van Allen Probes satellites and also observations from geosynchronous orbit made by the Magnetospheric Plasma Analyzer on board Los Alamos National Laboratory satellites. The fluxes of electrons from ~30 eV to 1 keV are quantified as a function of pitch‐angle, McIlwain L parameter, and local time for both quiet and active periods. Results indicate two sources for low‐energy electrons in this energy range: the low‐energy tail of the electron plasma sheet and the high‐energy tail of the dayside ionosphere. These populations are identified primarily as a result of their different pitch‐angle distributions. Field‐aligned outflows from the dayside ionosphere are observed at all L shells during quiet and active periods. Our results also demonstrate that the dayside electron field‐aligned fluxes at ~30 eV are particularly strong between L values of 6 and 7, indicating an enhanced source within the polar ionosphere. Key Points: Low‐energy electrons (tens to hundreds of eV) originate from two main sources: the ionosphere and the plasma sheet Low‐energy electrons pervade the inner magnetosphere where they can drive wave‐particle interactions Fluxes of electrons from ~30 eV to 1 keV are quantified by pitch‐angle, L value, and local time for both quiet and active periods